2000
DOI: 10.1007/s002640050004
|View full text |Cite
|
Sign up to set email alerts
|

Cementless cup supporter for protrusio acetabuli in patients with rheumatoid arthritis

Abstract: The MC cup supporter is an acetabular reinforcement ring for the Harris-Galante (HG) cementless porous-coated socket. This supporting ring has been used with autogenous bone graft since 1991 in the management of protrusio acetabuli in patients with rheumatoid arthritis (RA). We have reviewed 15 hips in 13 patients at an average of 53.6 months (range 24-84 months) after operation. The clinical results of total hip arthroplasty (THA) in protrusio acetabuli using this ring were satisfactory. All grafts appeared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
0
13
0
2
Order By: Relevance
“…None had failed at a mean followup of 4.2 years (range, 2-10 years). Matsuno et al [10] reported on 15 hips with rheumatoid arthritis which were treated with HG cementless porous-coated cups and supported by an acetabular rim ring and bone grafting. None had failed at a mean followup of 4.5 years (range, 2-7 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…None had failed at a mean followup of 4.2 years (range, 2-10 years). Matsuno et al [10] reported on 15 hips with rheumatoid arthritis which were treated with HG cementless porous-coated cups and supported by an acetabular rim ring and bone grafting. None had failed at a mean followup of 4.5 years (range, 2-7 years).…”
Section: Discussionmentioning
confidence: 99%
“…Mullaji and Marawar [12] reported a mean Harris hip score of 85 with 90% excellent or good results. Matsuno et al [10] reported satisfactory clinical results using the Japanese Orthopaedic Association (JOA) hip score. In our series, the clinical and functional results were excellent for uncemented cups, but the results were not as good as those seen with cemented cups alone without bone graft.…”
Section: Discussionmentioning
confidence: 99%
“…In 12 [9] were applied to six of these 12 hips, and two Trilogy acetabular components (Zimmer Co.) were used in two hips; the acetabular component in the remaining hip was secure and thus not revised. The patients were mobilized with crutches postoperatively without weight bearing during the first 4 weeks post-surgery, followed by partial weight bearing for the next 3 months.…”
Section: Methodsmentioning
confidence: 99%
“…Наиболее известно укрепляющее опорное кольцо, которое было разработано М. Мюллером в 1977 г., а пик его клинического применения в Европе начался после 1980 г. [1,15,20,21].…”
Section: выводыunclassified